PARKING NEEDS ANALYSIS AS PART OF THE FEASIBILITY ASSESSMENT FOR PARKING LOT DEVELOPMENT AT POLITEKNIK NEGERI UJUNG PANDANG - Andi Batari Angka; Erning Ertami Anton; Julvi Resli Datu Pagewang; Shafina Azizah Umar (Jurnal Infrastruktur, 2023)
The growth of motorbike and car users in several regions in Indonesia is quite high. This is because people's movement activities are increasing so the need for transportation is increasing. In Makassar City, the increase in transportation needs is also accompanied by an increase in the number of vehicles every year. Ujung Pandang State Polytechnic is one of the universities with quite high activity and interaction. This is because there is an increase in the number of students from year to year so the growth in vehicle users is greater. The increase in the number of vehicles has quite a big influence on the availability of parking lots, many parking locations have been converted into campus buildings, this condition causes the need for a place that functions to accommodate the number of vehicles each day or what is usually referred to as a parking lot. Based on the results of the research and discussion, it can be concluded that the parking capacity at the Ujung Pandang State Polytechnic is not able to accommodate the number of vehicles every day or what is usually referred to as a parking lot. Based on the results of the research and discussion, it can be concluded that the parking capacity at the Ujung Pandang State Polytechnic is not able to accommodate the number of vehicles every day. The results of the financial feasibility analysis show that the IRR value is greater than the interest rate, namely 14%, while the interest rate 13%. The payback period from the calculation results is 11 years, so the project to build a multi-story parking building facility is financially feasible to build. The need for parking space for the next 5 years on Ujung Pandang State Polytechnic cannot accommodate more vehicles, therefore this research designs a 2-story parking building that can solve the parking problem with an estimated cost of Rp. 55,651,200,000.00